Examining the impact of corruption in Malaysia using macroeconomic variables - Santhi, M. Silvam (2019)
Corruption is a serious issue faced by many countries. It can cause billion of losses in term of economic growth and development of a country. In Malaysia, many corruption cases have been reported which caused a decreased in GDP. Therefore, this study looks into the relationship between corruption and the macroeconomic variable in Malaysia and how transparency of corporate governance helps to reduce corruption. The data used for this study are from 2009 to 2018 with inflation, GDP growth and unemployment as the independent variable which affecting the corruption cases in Malaysia. Through this study, it is found that the corruption has affected the economy growth over the years. As for Malaysia, to become a developed country, the existing corruption cases should be investigated further and find solution. This is a step in preventing more corruption from occurring in the county. This study also recommend that the policymaker should take immediate action in amending the current policy by adapting a higher transparency element in all transactions and practices in both public and private sector as the corruption is detrimental to the country economic growth.